The effects of a single night of complete and partial sleep deprivation on physical and cognitive performance: A Bayesian analysis. Issue 23 (2nd December 2019) - Cullen, Tom; Thomas, Gavin; Wadley, Alex J.; Myers, Tony
ABSTRACT: This study investigated the effects of complete and partial sleep deprivation on multiple aspects of athletic performance. Ten males completed a cognitive function test, maximal handgrip strength, countermovement jump (CMJ) and a 15 min all out cycling test to assess aerobic performance. These tests were performed following 3 different sleep conditions; normal sleep (CON), a 4 hr sleep opportunity (PART) and complete sleep deprivation (DEP). Data were analysed using a Bayesian multi-level regression model to provide probabilities of impairment (p = %). Aerobic performance, CMJ and handgrip strength were impaired by 11.4% (p = 100%), 10.9% (p = 100%) and 6% (p = 97%) following DEP, while aerobic performance and CMJ were highly likely impaired by 4.1% (p = 90%) and 5.2% (p = 94%) following PART. Cognitive reaction time was not impacted by PART or DEP. In contrast the accuracy of responses was highly likely impaired by 2% (91) following DEP, while there was less certainty of impaired accuracy following PART (−1%, p = 73). Multiple aspects of physical and cognitive performance were impacted by sleep deprivation. The greatest detrimental effects were seen for aerobic performance and CMJ. Partial sleep deprivation equating to 4 hrs of sleep causes subtle, but potentially important negative impairments on athletic performance.